2020
DOI: 10.3390/ijerph17207592
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Cancers Attributable to Infection in the Republic of Korea: A Prevalence-Based Study

Abstract: Infection is a major cause of cancers. We estimated the economic burden of cancers attributable to infection in 2014 in Korea, where cancer causing infection is prevalent, but the economic burden of it has never been examined. Cancer patients were defined as those having made medical claims as recorded by the National Health Insurance Service, which is a mandatory insurance for all citizen. We multiplied the costs by the population-attributable fraction for each type of cancer. The study included direct and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The number of incident cancer cases was estimated at 229,180, of which 27.8% of cancer-related deaths occurred between 2011 and 2016 ( 3 ). The cancer-related economic burden was reported exhibited an average 8.9% annual growth rate in 2010 ( 4 ), accounting for 0.23% of the national gross domestic product and 1.36% of national healthcare expenditure in 2014 ( 5 ) and, in terms of the total cost, $1 was equal to 1,131.52 won in 2015, according to Statistics Korea ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The number of incident cancer cases was estimated at 229,180, of which 27.8% of cancer-related deaths occurred between 2011 and 2016 ( 3 ). The cancer-related economic burden was reported exhibited an average 8.9% annual growth rate in 2010 ( 4 ), accounting for 0.23% of the national gross domestic product and 1.36% of national healthcare expenditure in 2014 ( 5 ) and, in terms of the total cost, $1 was equal to 1,131.52 won in 2015, according to Statistics Korea ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there is significant economic burden associated with infection-attributable cancers. A Korean study reported direct costs of these cancers amounting to USD 676.9 million and indirect costs amounting to USD 2.57 billion in 2014, which accounted for 0.23% of the gross domestic product and 1.36% of the healthcare expenditure [9].…”
Section: Introductionmentioning
confidence: 99%